Starategi Pemasaran Bank BTN Syariah Untuk Meningkatkan Jumlah Nasabah Terhadap Produk KPR Pada BTN Syariah KCP Setiabudi Mengunakan Analisis Soar - Ibnu Syawali Manurung (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The high demand for new houses combined with the large number of marriages has led to an increase in demand for livable houses. The role of BTN as a housing credit (KPR) provider entrusted by the state takes an important role as the main capital in Indonesia. BTNS SETIA BUDI is one of the BTN banks located in the city of Medan, it contains sharia principles, providing the best service to attract mortgage loan customers using sharia principles. Therefore, BTNS Setia Budi must improve its marketing strategy as an important capital to support mortgage financing. The author took the title of this research to determine the effectiveness of BTNS's marketing strategy using SOAR analysis with a qualitative method taking sources of information from existing journals and direct interviews with BTNS Setia Budi staff.